ANALISIS PENGARUH ROA,ROE,BOPO,DAN SUKU BUNGA TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH PADA PERBANKAN SYARIAH - Cahyani, Wulandari Nur; Falah, Syaikhul; Wijayanti, Ratna Yulia (MALIA: Journal of Islamic Banking and Finance, 2017)
This study aimed to analyze the influence of ROA, ROE, BOPO, and the Interest Rate on the rate of profit sharing Mudharabah deposits. The population in this study were allIslamic Banks in Indonesia which consists of 11 Islamic Banks.The selection of the sample in this study is purposive sampling according to the criteria set out which are Islamic Banks that published complete financial statements quarterly of the period 2011-2013. The analytical method used is multiple linear regression analysis to examine the relationship / influence of one variable to another variable. The results showed that ROA, ROE, BOPO, and the interest rate affect the level of profit sharing mudharabah deposits simultaneously. Partially, ROA and interest rate do not affect the level of profit sharing mudharabah deposits which is shown by significant value which is greater than 0. 05. While the ROE variable has significant negative influence and the BOPO has significant positive influence on the rate of profit sharing mudharabah deposits. Keywords:assets,equity,sharing